Folklore of the Origins of Dukuh Tambak and Pasar Tambak in Sragen and its Local Wisdom Values - Silvi Mardiana; Kundharu Saddhono; Edy Suryanto (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
Folklore as a literary work reflects the lives of people, including the origins of a particular place. This research aims to: (1) describe the folklore of the origin of Dukuh Tambak in Sragen, (2) describe the folklore of the origin of Pasar Tambak in Sragen, and (3) identify the value of local wisdom in the two stories. The method used is qualitative with a literary anthropology approach, using purposive sampling technique to select two interrelated stories. Data validity was tested by source triangulation and data analysis using a flow model analysis. The results show that the origin stories of Dukuh Tambak and Pasar Tambak describe the historical journey of the spread of Islam around the Bengawan Solo River, with Joko Tingkir and Kanjeng Raden Tumenggung Tambak Yudho as the main characters in Dukuh Tambak. Meanwhile, Pasar Tambak, spearheaded by Prince Giri Noto, continues the tradition of generosity and honesty in social interaction. From both stories, local wisdom values were found: (1) religiosity value, (2) social value, (3) leadership and responsibility value, (4) hard work value, (5) honesty value, and (6) cultural value.